An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis